2022
DOI: 10.1088/1755-1315/1096/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive photodetectors on the basis of Au-oxide-n-GaP0.4As0.6

Abstract: This paper presents the results of studies of the photoelectric properties of Au-oxide-n-GaP0.4As0.6 nanostructures with different thicknesses of oxide layer (10-100Å) in the visible and ultraviolet regions of the spectrum. As a result, photodetectors of UV radiation based on Au-oxide-n-GaAs0.6P0.4 nanostructures with an optimal thickness of the oxide layer (δ=30-60 Å) were developed. The creation of highly effective photodetectors of solar ultraviolet radiation (λ=280-400 nm, hυ=3,1-4,43 eV) for ecological pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In the compound CuFeS2 this value is small,  ~ 1 cm 2 V -1 s -1 , and almost independent of temperature in the interval measured. Such behavior is characteristic of a large-radius magnetic polaron (ferron) in antiferromagnetic, when the conduction electron creates a ferromagnetic region of radius around itself [25][26][27]. The results obtained are consistent with the results obtained on samples prepared using a conventional solid-phase reaction, as described earlier.13) The author noted that such samples give the Seebeck effect practically independent of temperatures above 100 K and show a large negative value at room temperature.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the compound CuFeS2 this value is small,  ~ 1 cm 2 V -1 s -1 , and almost independent of temperature in the interval measured. Such behavior is characteristic of a large-radius magnetic polaron (ferron) in antiferromagnetic, when the conduction electron creates a ferromagnetic region of radius around itself [25][26][27]. The results obtained are consistent with the results obtained on samples prepared using a conventional solid-phase reaction, as described earlier.13) The author noted that such samples give the Seebeck effect practically independent of temperatures above 100 K and show a large negative value at room temperature.…”
Section: Resultssupporting
confidence: 85%
“…Therefore, taking these results and the small value of the electron concentration at low temperatures as the basis, we concluded that CuFeS2 belongs. to this class of compounds [19][20][21][22][23][24][25][26]. Similar investigations of CuFeTe, also reveal the existence of the power behaviour of the R(T), o(T) and n(T) values (figure 2).…”
Section: Resultsmentioning
confidence: 54%